Simultaneous estimation of Rabeprazole and Mosapride by RP-HPLC method in tablet dosage form - Srikanth Choudary Pallothu; Jogu Chandrudu; Sriram. N (International Journal of Pharmacy and Analytical Research, 2022)
A simple, selective, accurate high Performance Liquid Chromatographic (HPLC) method was developed and validated for the analysis of Rabeprazole and Mosapride in Tablet dosage form. Chromatographic separation achieved isocratically on Inertsil C18, ODS column using mobile phase Acetonitrile 100%, with flow rate of 1.0ml/min with UV detection at 276nm. The retention time of Rabeprazole and Mosapride are 2.951 and 4.195 respectively. The developed method was validated in terms of accuracy, precis ion, linearity, limit of detection, limit of quantitation. This study aimed at developing and validating an HPLC method, being simple, accurate and selective, and the proposed method can be used for the estimation of these drugs in combined dosage forms